CRISPR/Cas9-engineering of HMC-1.2 cells renders a human mast cell line with a single D816V-KIT mutation: An improved preclinical model for research on mastocytosis - Bandara, Geethani; Falduto, Guido H.; Luker, Andrea; Bai, Yun; Pfeiffer, Annika; Lack, Justin; Metcalfe, Dean D.; Olivera, Ana (Frontiers in Immunology, 2023)
The HMC-1.2 human mast cell (huMC) line is often employed in the study of attributes of neoplastic huMCs as found in patients with mastocytosis and their sensitivity to interventional drugs in vitro and in vivo. HMC-1.2 cells express constitutively active KIT, an essential growth factor receptor for huMC survival and function, due to the presence of two oncogenic mutations (D816V and V560G). However, systemic mastocytosis is commonly associated with a single D816V-KIT mutation. The functional consequences of the coexisting KIT mutations in HMC-1.2 cells are unknown. We used CRISPR/Cas9 engineering to reverse the V560G mutation in HMC-1.2 cells, resulting in a subline (HMC-1.3) with a single mono-allelic D816V-KIT variant. Transcriptome analyses predicted reduced activity in pathways involved in survival, cell-to-cell adhesion, and neoplasia in HMC-1.3 compared to HMC-1.2 cells, with differences in expression of molecular components and cell surface markers. Consistently, subcutaneous inoculation of HMC-1.3 into mice produced significantly smaller tumors than HMC-1.2 cells, and in colony assays, HMC-1.3 formed less numerous and smaller colonies than HMC-1.2 cells. However, in liquid culture conditions, the growth of HMC-1.2 and HMC-1.3 cells was comparable. Phosphorylation levels of ERK1/2, AKT and STAT5, representing pathways associated with constitutive oncogenic KIT signaling, were also similar between HMC-1.2 and HMC-1.3 cells. Despite these similarities in liquid culture, survival of HMC-1.3 cells was diminished in response to various pharmacological inhibitors, including tyrosine kinase inhibitors used clinically for treatment of advanced systemic mastocytosis, and JAK2 and BCL2 inhibitors, making HMC-1.3 more susceptible to these drugs than HMC-1.2 cells. Our study thus reveals that the additional V560G-KIT oncogenic variant in HMC-1.2 cells modifies transcriptional programs induced by D816V-KIT, confers a survival advantage, alters sensitivity to interventional drugs, and increases the tumorigenicity, suggesting that engineered huMCs with a single D816V-KIT variant may represent an improved preclinical model for mastocytosis.